Secondary battery and electric device
Patent Information
- Application Number
- CN202610314692.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-03-13
- Publication Date
- 2026-09-11
- Estimated Expiration
- 2046-03-13
AI Technical Summary
过度的锂镍混排(如在三元材料的晶体结构中过多的Ni占据Li的位置)则可能导致正极材料与电解液之间的副反应增加,使三元材料中过渡金属元素的溶出增加,破坏负极表面,导致二次电池的内部阻抗增加,二次电池的循环性能下降
本申请通过在电解液中引入环状硫酸酯类化合物,并综合调控镍钴三元材料的相比率a、负极材料层的厚度与负极材料的粒径Dv50之间的比值b、电解液中硫酸酯官能团的质量百分含量c,使a/(b×c)在适宜范围内,可以降低二次电池内部的阻抗,提高二次电池的快充性能,使正极片和负极片不易与电解液发生副反应,提高二次电池的循环性能。
Smart Images

Figure SMS_20 
Figure SMS_21 
Figure SMS_22
Abstract
Description
Technical Field
[0001] This application relates to the field of secondary battery technology, specifically to a secondary battery and an electrical device. Background Technology
[0002] Ternary lithium-ion rechargeable batteries are high-performance lithium-ion batteries that use ternary materials as the positive electrode material, exhibiting high energy density and high voltage. In ternary materials (such as lithium nickel cobalt manganese oxide or lithium nickel cobalt aluminum oxide), lithium ions and transition metal ions (such as nickel, cobalt, manganese, or aluminum) should ideally occupy specific lattice positions, forming an ordered layered structure. However, during the charge-discharge cycle of the rechargeable battery, due to the influence of various factors (such as temperature, voltage, current density, etc.), lithium ions and nickel ions in the ternary material may migrate, causing their positions in the lattice to become disordered, i.e., lithium-nickel mixing. Excessive lithium-nickel mixing (such as too much Ni occupying Li positions in the crystal structure of the ternary material) may lead to an increase in side reactions between the positive electrode material and the electrolyte, increasing the dissolution of transition metal elements in the ternary material, damaging the negative electrode surface, resulting in an increase in the internal impedance of the rechargeable battery and a decrease in its cycle performance.
[0003] In view of this, it is indeed necessary to provide a technical solution to the above problems. Summary of the Invention
[0004] Based on the deficiencies of the existing technology, the purpose of this application is to provide a secondary battery and an electrical device.
[0005] To achieve the above objectives, the technical solution adopted in this application is as follows: The first aspect of this application provides a secondary battery, comprising a battery cell and an electrolyte. The battery cell includes a positive electrode and a negative electrode. The positive electrode includes a positive electrode material layer, which comprises a nickel-cobalt ternary material. The specific gravity of the nickel-cobalt ternary material is a. The nickel-cobalt ternary material comprises primary particles, each primary particle including a core and a surface layer disposed on the outer surface of the core. The diameter of the primary particles is d, in nm. The surface layer of the primary particles is a rock salt phase, the thickness of which is e, in nm. a is e / d × 100%. The negative electrode sheet includes a negative electrode material layer, the negative electrode material layer includes a negative electrode material, the ratio between the thickness of the negative electrode material layer and the particle size Dv50 of the negative electrode material is b, and the units of the thickness of the negative electrode material layer and the particle size Dv50 of the negative electrode material are both μm; The electrolyte comprises cyclic sulfate ester compounds, and the mass percentage of sulfate ester functional groups in the electrolyte is c. The secondary battery satisfies: 0.0010≤a / (b×c)≤220.5298; The cyclic sulfate compounds include compounds represented by Formula I; in Formula I, R1, R2, R3 and R4 each independently include at least one of the following groups represented by Formula II, hydrogen atoms, alkyl groups of 1 to 6 carbon atoms, halogen atoms, haloalkyl groups of 1 to 3 carbon atoms, alkoxy groups of 1 to 3 carbon atoms, haloalkoxy groups of 1 to 3 carbon atoms, alkenyl groups, ester groups, cyano groups, and sulfonic acid groups; In Formula II, R5 and R6 each independently include at least one of the following groups as shown in Formula III: a hydrogen atom, an alkyl group of 1 to 6 carbon atoms, a halogen atom, a haloalkyl group of 1 to 3 carbon atoms, an alkoxy group of 1 to 3 carbon atoms, a haloalkoxy group of 1 to 3 carbon atoms, an alkenyl group, an ester group, a cyano group, and a sulfonic acid group. In Formula III, R7 and R8 each independently include at least one of the following: hydrogen atom, alkyl group of 1 to 6 carbon atoms, halogen atom, haloalkyl group of 1 to 3 carbon atoms, alkoxy group of 1 to 3 carbon atoms, haloalkoxy group of 1 to 3 carbon atoms, alkenyl group, ester group, cyano group, and sulfonic acid group. Formula I, Formula II, Formula III.
[0006] The second aspect of this application provides an electrical device, which includes the secondary battery provided in the first aspect of this application.
[0007] Compared with the prior art, the beneficial effects of this application are as follows: This application introduces cyclic sulfate compounds into the electrolyte and comprehensively controls the ratio a of nickel-cobalt ternary materials, the ratio b between the thickness of the negative electrode material layer and the particle size Dv50 of the negative electrode material, and the mass percentage of sulfate functional groups in the electrolyte, so that a / (b×c) is within a suitable range. This reduces the internal impedance of the secondary battery, improves the fast-charging performance of the secondary battery, makes the positive and negative electrode plates less likely to undergo side reactions with the electrolyte, and improves the cycle performance of the secondary battery. Detailed Implementation
[0008] To better illustrate the purpose, technical solution, and advantages of this application, the following description, in conjunction with specific embodiments and comparative examples, aims to provide a detailed understanding of the content of this application, rather than to limit its scope. All other embodiments obtained by those skilled in the art without inventive effort are within the protection scope of this application.
[0009] In this application, the technical features described in an open-ended manner include both closed technical solutions consisting of the listed features and open technical solutions that include the listed features.
[0010] In this application, numerical ranges are referred to as continuous unless otherwise specified, and include the minimum and maximum values of the range, as well as every value between the minimum and maximum values. Furthermore, when the range refers to integers, it includes every integer between the minimum and maximum values of the range. Additionally, when multiple ranges are provided to describe a feature or characteristic, the ranges may be merged. In other words, unless otherwise specified, all ranges disclosed herein should be understood to include any and all subranges to which they are incorporated.
[0011] In the description of this application, the term "and / or" is merely a description of the relationship between related objects, indicating that three relationships can exist. For example, A and / or B can represent: A existing alone, A and B existing simultaneously, or B existing alone. Additionally, the character " / " in this document generally indicates that the preceding and following related objects have an "or" relationship.
[0012] Furthermore, the terms "first," "second," and "third" are used for descriptive purposes only and should not be construed as indicating or implying relative importance or implicitly specifying the number of technical features indicated. Thus, a feature defined as "first," "second," or "third" may explicitly or implicitly include at least one of that feature. In the description of this application, "multiple" means at least two, such as two, three, etc., unless otherwise explicitly specified.
[0013] In this application, the terms "secondary battery", "lithium secondary battery", and "lithium-ion secondary battery" all have the same meaning and refer to lithium-ion secondary batteries, which typically include electrode components (such as positive electrode plates, negative electrode plates, and separators), a container (such as a housing) that houses the electrode components, and an electrolyte.
[0014] In a first aspect, this application provides a secondary battery, including a battery cell and an electrolyte. The battery cell includes a positive electrode and a negative electrode. The positive electrode includes a positive electrode material layer, which comprises a nickel-cobalt ternary material with a specific gravity of a. The nickel-cobalt ternary material comprises primary particles, each primary particle including a core and a surface layer disposed on the outer surface of the core. The diameter of the primary particles is d (in nm). The surface layer of the primary particles is a rock salt phase with a thickness of e (in nm). a is e / d × 100%. The negative electrode sheet includes a negative electrode material layer, the negative electrode material layer includes a negative electrode material, the ratio between the thickness of the negative electrode material layer and the particle size Dv50 of the negative electrode material is b, and the units of the thickness of the negative electrode material layer and the particle size Dv50 of the negative electrode material are both μm; The electrolyte comprises cyclic sulfate ester compounds, and the mass percentage of sulfate ester functional groups in the electrolyte is c. The secondary battery satisfies: 0.0010≤a / (b×c)≤220.5298; The cyclic sulfate compounds include compounds represented by Formula I; in Formula I, R1, R2, R3 and R4 each independently include at least one of the following groups represented by Formula II, hydrogen atoms, alkyl groups of 1 to 6 carbon atoms, halogen atoms, haloalkyl groups of 1 to 3 carbon atoms, alkoxy groups of 1 to 3 carbon atoms, haloalkoxy groups of 1 to 3 carbon atoms, alkenyl groups, ester groups, cyano groups, and sulfonic acid groups; In Formula II, R5 and R6 each independently include at least one of the following groups as shown in Formula III: a hydrogen atom, an alkyl group of 1 to 6 carbon atoms, a halogen atom, a haloalkyl group of 1 to 3 carbon atoms, an alkoxy group of 1 to 3 carbon atoms, a haloalkoxy group of 1 to 3 carbon atoms, an alkenyl group, an ester group, a cyano group, and a sulfonic acid group. In Formula III, R7 and R8 each independently include at least one of the following: hydrogen atom, alkyl group of 1 to 6 carbon atoms, halogen atom, haloalkyl group of 1 to 3 carbon atoms, alkoxy group of 1 to 3 carbon atoms, haloalkoxy group of 1 to 3 carbon atoms, alkenyl group, ester group, cyano group, and sulfonic acid group. Formula I, Formula II, Formula III.
[0015] For example, a / (b×c) can be 0.0010, 0.0050, 0.01, 0.05, 0.1, 0.5, 1, 5, 10, 15, 20, 25, 30, 35, 40, 45, 50, 55, 60, 65, 70, 75, 80, 85, 90, 95, 100, 105, 110, 115, 120, 125, 130, 135, 140, 145, 150, 155, 160, 165, 170, 175, 180, 185, 190, 195, 200, 205, 210, 215, 220, 220.5298 or a range of any two sets of values.
[0016] The inventors discovered that introducing cyclic sulfate compounds into the electrolyte can significantly improve the integrity of the film formed on the positive electrode side, reduce side reactions between the electrolyte and the positive electrode, reduce the consumption of active lithium, and improve the cycle performance of the secondary battery. However, excessive addition of cyclic sulfate compounds can lead to increased interfacial impedance of the secondary battery, affecting its fast-charging performance. Therefore, simply increasing the amount of cyclic sulfate compounds cannot simultaneously achieve both fast-charging and cycle performance of the secondary battery.
[0017] This application reduces the number of negative electrode material particles per unit thickness by adjusting the ratio between the thickness of the negative electrode material layer and the particle size Dv50 of the negative electrode material, thereby suppressing side reactions at the negative electrode. Furthermore, by adjusting the specific ratio α of the nickel-cobalt ternary material, the stability of the nickel-cobalt ternary material itself is improved, thereby reducing the amount of cyclic sulfate compounds added to the electrolyte.
[0018] To balance the fast-charging and cycle performance of secondary batteries, it is necessary to simultaneously control the relative ratio (a) of nickel-cobalt ternary materials, the ratio (b) between the thickness of the negative electrode material layer and the particle size (Dv50) of the negative electrode material, and the mass percentage (c) of sulfate ester functional groups in the electrolyte. This keeps a / (b×c) within a suitable range, thereby reducing the positive electrode interface impedance while suppressing the negative electrode side reactions, achieving a balance between the fast-charging and cycle performance of the secondary battery.
[0019] In some embodiments, the number of sulfate groups in the compound with the structure shown in Formula I is n, where n is a positive integer from 2 to 4.
[0020] The inventors discovered that by adjusting the number of sulfate groups in the compound with the structure shown in Formula I within a suitable range, the film resistance inside the secondary battery can be reduced.
[0021] In some embodiments, at least one of R2 and R4 is a hydrogen atom, and R1 and R3 each independently include at least one of the following: a group represented by Formula II, a hydrogen atom, an alkyl group of 1 to 6 carbon atoms, a halogen atom, a haloalkyl group of 1 to 3 carbon atoms, and an alkoxy group of 1 to 3 carbon atoms.
[0022] In some embodiments, R1 and R3 are the same substituents and are selected from any one of the groups shown in Formula II, hydrogen atoms, alkyl groups of 1 to 6 carbon atoms, halogen atoms, haloalkyl groups of 1 to 3 carbon atoms, and alkoxy groups of 1 to 3 carbon atoms.
[0023] In some embodiments, R1 and R3 are selected from -CH3, -C2H5, -C3H7, -CH=CH2, -CH2-CH=CH2, -CH=CH-CH3, -O-CH3, -O-C2H5, -O-C3H7, -F, -Cl, -Br, -I, -CF3, -CCl3, -CBr3, -C2F5, -C2Cl5, -C2Br5, -C3F7, -C3Cl7, -C3Br7, Any one of the groups shown.
[0024] In some embodiments, the cyclic sulfate compound includes at least one of the following compounds: , , , , , .
[0025] In some implementations, 0.0016 ≤ a / (b×c) ≤ 73.2353. When a / (b×c) is in the range of 0.0016 to 73.2353, the secondary battery exhibits better fast-charging and cycle performance.
[0026] In some implementations, 0.1% ≤ a ≤ 2%. For example, a can be 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1.0%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2.0%, or a range of any two sets of values therein.
[0027] The inventors discovered that during the synthesis of nickel-cobalt ternary materials, after high-temperature sintering, the layered phase on the surface of the nickel-cobalt ternary material particles easily transforms into a rock salt phase, thus forming particles with a rock salt phase on the surface and a layered phase in the core. The rock salt phase has a dense three-dimensional structure, stable ionic valence states, and high chemical inertness, making it less prone to side reactions with the electrolyte, but it has higher impedance. The layered phase, on the other hand, continuously generates highly active surfaces, easily reacting with the electrolyte, exhibiting poor stability, but low impedance. The specific ratio 'a' of the nickel-cobalt ternary material reflects the relative ratio of the thickness of the surface rock salt phase to the diameter of the primary particles. A larger 'a' indicates a higher proportion of surface rock salt phase thickness. The rock salt phase itself has poor conductivity, increasing the impedance at the positive electrode interface and thus limiting the fast-charging capability of the secondary battery. Conversely, a smaller 'a' indicates a lower proportion of surface rock salt phase thickness, making the nickel-cobalt ternary material particles more prone to side reactions with the electrolyte, increasing the consumption of active lithium, and deteriorating the cycle performance of the secondary battery. This application, by adjusting 'a' to meet the above-mentioned range, can balance the conductivity and stability of nickel-cobalt ternary materials, reduce side reactions between nickel-cobalt ternary material particles and electrolyte, thereby improving the fast-charging performance and cycle performance of secondary batteries.
[0028] For further optimization, 0.12% ≤ a ≤ 1.5%.
[0029] This application can control the value of 'a' by adjusting the nickel content in the nickel-cobalt ternary material, the sintering temperature and sintering time during the preparation process of the nickel-cobalt ternary material.
[0030] This application does not limit the detection method for 'a', and it can be detected using conventional methods in the art. For example, the following method is used for detection: Discharge the secondary battery to the lower limit voltage of 2.5V, disassemble the secondary battery, and remove the positive electrode plate; The cathode sheet was subjected to TEM scanning. Random blind scanning high-magnification (100Kx~200Kx, i.e., 100,000 to 200,000 times) transmission electron microscopy was performed on the edges of the nickel-cobalt ternary material particles to obtain lattice fringe images at the particle edges. The lattice fringe spacing at the edges was measured using MEARSURE NANO software. The distribution area with a lattice fringe spacing of 0.207±0.01nm (the lattice spacing of Fd3m in Ni-O) can be identified as Ni-O in the Fd3m (rock salt phase) space group. In addition, the inner side of the Fd3m phase refers to the layered phase (Fr3m), and the lattice fringe spacing of the layered phase is selected as 0.473 ± 0.01nm. Five particles were taken, and the thickness of Fd3m (rock salt phase) at 10 locations on the same particle was measured. The average value was then taken to obtain the average thickness of Fd3m (rock salt phase) (denoted as e). Then the magnification of the transmission electron microscope was adjusted to 2kx (i.e., 2000 times), and MEARSURE was used to measure the thickness of the Fd3m (rock salt phase) at the same location. The NANO software was used to collect the particle diameter (denoted as d) of the nickel-cobalt ternary material using the cross-line method. The a1% of the particle was calculated according to the formula (1); a1%=(e / d)×100% (1). The a1% of 5 particles were measured respectively, and the average value was taken as a.
[0031] In some implementations, 1.5 ≤ b ≤ 40.
[0032] For example, b can be 1.5, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, or a range consisting of any two sets of values.
[0033] The inventors discovered that a smaller ratio (b) between the thickness of the negative electrode material layer and the particle size (Dv50) of the negative electrode material results in fewer particles of negative electrode material per unit thickness of the negative electrode material layer, greater inter-particle impedance, and poorer fast-charging performance of the secondary battery. Conversely, a larger b results in more particles of negative electrode material per unit thickness of the negative electrode material layer, increasing the contact area between the particles and the electrolyte, making the negative electrode material more prone to side reactions with the electrolyte, thereby reducing the cycle performance of the secondary battery. This application, by adjusting b within the above range, achieves a moderate number of negative electrode material particles per unit thickness of the negative electrode material layer. This reduces the inter-particle impedance while maintaining a moderate contact area between the particles and the electrolyte, preventing an excessively large contact area that would lead to a surge in side reactions between the particles and the electrolyte. This improves both the fast-charging performance and the cycle performance of the secondary battery.
[0034] For a further preferred value, 2≤b≤35.
[0035] This application allows for the control of the value of b by adjusting the pressure during cold pressing or by controlling the particle size of the initial negative electrode material particles during the preparation of the negative electrode sheet.
[0036] This application does not limit the detection method for the value of b; it can be detected using conventional methods in the art. For example, the following method is used for detection: The secondary battery was discharged to the lower limit voltage of 2.5V, the secondary battery was disassembled, the negative electrode sheet was taken out, and dried at 60℃ for 8 hours. The dried negative electrode sheet was then measured under a scanning electron microscope to obtain the thickness h of the negative electrode material layer, in μm. Discharge the secondary battery to the lower limit voltage of 2.5V, disassemble the secondary battery, remove the negative electrode, dry it at 60℃ for 24 hours, scrape off the powder, take 1g of powder and use a laser particle size distribution measuring instrument (Mastersizer 3000) to measure the particle size distribution according to the particle size distribution laser diffraction method (specific steps refer to GB / T19077-2016). The particle size corresponding to the cumulative particle size distribution percentage reaching 50% is Dv50, in μm; The value of b can be calculated using the formula b=h / Dv50.
[0037] In some implementations, 0.001% ≤ c ≤ 2.7%. For example, c can be 0.001%, 0.005%, 0.01%, 0.05%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1.0%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2.0%, 2.1%, 2.2%, 2.3%, 2.4%, 2.5%, 2.6%, 2.7%, or a range of any two of these values.
[0038] The inventors discovered that by adjusting the mass percentage c of sulfate functional groups in the electrolyte to the above-mentioned range, the integrity of the film formed on the positive electrode side can be improved, the side reactions between the electrolyte and the positive electrode sheet can be reduced, the consumption of active lithium can be reduced, the cycle performance of the secondary battery can be improved, and the increase in the interfacial impedance of the secondary battery due to excessive addition of cyclic sulfate compounds can be avoided, thereby ensuring the fast charging performance of the secondary battery.
[0039] For further optimization, 0.01% ≤ c ≤ 2.5%.
[0040] The value of c can be controlled by adjusting the amount of cyclic sulfate compounds added or by adjusting the number of sulfate groups in the structural formula of the cyclic sulfate compounds during the preparation of the electrolyte.
[0041] This application does not limit the detection method for c; it can be detected using conventional methods in the art. For example, the following method is used for detection: The secondary battery under test was discharged using a battery charging and discharging device. Discharge conditions: current 0.33C, cutoff voltage 2.5V. After recording the battery number / barcode, the battery was disassembled and the electrolyte collected in a glove box (where the molar content of H2O ≤ 0.1ppm and the molar content of O2 ≤ 0.1ppm). There are three methods for collecting the electrolyte: After removing the battery cover, ① if there is free electrolyte, collect it into a 5mL sample tube using a pipette and seal it with sealing tape to prevent leakage. ② if there is no free electrolyte, a hydraulic press (Beijing Heng'ao Technology Co., Ltd.'s FY-30 hydraulic press) can be used to continuously pressurize until free electrolyte appears. Collect the electrolyte into a sample tube and seal it. ③ Add an appropriate amount of dichloromethane extractant to the battery and record the dichloromethane content. After adding dichloromethane, put the battery into an aluminum-plastic bag and seal it with a heat sealer. Transfer it to an ultrasonic oscillator and oscillate for 12 hours to allow the electrolyte in the electrode to mix thoroughly with the dichloromethane. Then, use a pipette to draw the mixture of dichloromethane and electrolyte into a 5mL sample tube and seal the sample tube with sealing glue. The collected electrolyte samples were injected into an Agilent Intuvo 9000 gas chromatograph-mass spectrometer using a microsyringe for testing, and GC-MS spectra were obtained. Cyclic sulfate ester compound standards were dissolved in EMC solvent to prepare solutions of different concentrations, and these solutions were injected into the Agilent Intuvo 9000 gas chromatograph-mass spectrometer to obtain standard GC-MS spectra. The GC-MS spectra of the electrolyte samples were compared with the standard GC-MS spectra to confirm whether the electrolyte samples contained the corresponding cyclic sulfate ester compounds, and their relative molar mass M1 was obtained. Based on the determined structural formula of the cyclic sulfate ester compound, determine the number of sulfate ester groups and the relative molar mass M2 of the sulfate ester groups in the structural formula; The mass percentage (denoted as C) of cyclic sulfate ester compounds in the electrolyte was obtained by using GC gas chromatography based on the measured components. The mass percentage c of sulfate groups in the electrolyte is calculated using the following formula: c = (M2 / M 1) ×n×C.
[0042] In some embodiments, the diameter of the primary particle is 2000 nm to 20000 nm, and / or the thickness of the surface layer of the primary particle is 0.8 nm to 50 nm.
[0043] For example, the diameter (i.e., d) of the primary particle can be 2000nm, 3000nm, 4000nm, 5000nm, 6000nm, 7000nm, 8000nm, 9000nm, 10000nm, 11000nm, 12000nm, 13000nm, 14000nm, 15000nm, 16000nm, 17000nm, 18000nm, 19000nm, 20000nm, or any of these. The range consisting of two sets of values; the thickness (e) of the surface layer of the primary particle can be 0.8nm, 1nm, 2nm, 3nm, 4nm, 5nm, 6nm, 7nm, 8nm, 9nm, 10nm, 12nm, 15nm, 18nm, 20nm, 22nm, 25nm, 28nm, 30nm, 32nm, 35nm, 38nm, 40nm, 42nm, 45nm, 48nm, 50nm, or any two sets of values.
[0044] The inventors discovered through research that by adjusting d and e to appropriate ranges, this application improves the stability of the nickel-cobalt ternary material itself while reducing its impedance, thereby balancing the cycle performance and fast-charging performance of the secondary battery.
[0045] In some embodiments, the particle size Dv50 of the nickel-cobalt ternary material is 2μm to 20μm.
[0046] For example, the particle size Dv50 of the nickel-cobalt ternary material can be 2μm, 3μm, 4μm, 5μm, 6μm, 7μm, 8μm, 9μm, 10μm, 11μm, 12μm, 12μm, 14μm, 15μm, 16μm, 17μm, 18μm, 19μm, 20μm or any two sets of values therein.
[0047] Through research, the inventors discovered that by adjusting the particle size of the nickel-cobalt ternary material to a suitable range, this application can balance the impedance between nickel-cobalt ternary material particles and the contact area between the nickel-cobalt ternary material particles and the electrolyte, thereby taking into account both the cycle performance and fast charging performance of the secondary battery.
[0048] In some embodiments, the compaction density of the positive electrode is 3 g / cm³. 3 ~4g / cm 3 .
[0049] For example, the compaction density of the positive electrode sheet can be 3 g / cm³. 3 3.1g / cm 3 3.2g / cm 3 3.3g / cm 3 3.4g / cm 33.5g / cm 3 3.6g / cm 3 3.7g / cm 3 3.8g / cm 3 3.9g / cm 3 4g / cm 3 Or a range consisting of any two sets of values.
[0050] In this application, the compaction density of the positive electrode sheet can be determined by the following method: The secondary battery was discharged at 0.33C to the lower limit voltage of 2.5V. The secondary battery was disassembled, and the positive electrode sheet was removed. The positive electrode sheet was soaked in dimethyl carbonate (DMC) solution for 4 hours and then dried. The pretreated positive electrode sheet was cut into circular pieces of fixed area using a punching machine. The area was recorded as S0. Three circular pieces were taken as parallel samples, and the mass of the three circular pieces was weighed using an electronic balance. The average value was recorded as M1. The thickness of the active material layer in the three circular pieces (i.e., the total thickness excluding the current collector) was measured using a micrometer. The average value was recorded as H. Finally, an appropriate amount of deionized water was dropped onto each of the three circular pieces. The coating on the circular pieces was gently wiped off with lint-free paper to expose the copper foil. The pieces were left to stand at room temperature (or dried) for 10 minutes. After the copper foil was dried, the mass of the three copper foil pieces was weighed. The average value was recorded as M0. The compaction density A of the positive electrode material layer was calculated according to the following formula: A = (M1 - M0) / (H × S0).
[0051] In some embodiments, the nickel-cobalt ternary material is a nickel-cobalt-manganese ternary material.
[0052] The general chemical formula of the nickel-cobalt-manganese ternary material is LiNi. x Co y Mn z M f O2, where 0.1 < x < 1, 0.1 < y < 1, 0.1 < z < 1, and x + y + z + f = 1, M is a dopant element, and M includes at least one of Al, Mg, Ti, Zr, B, P, Nb, Ta, W, Zr, and V.
[0053] Further preferred values are 0.4 ≤ x ≤ 0.7 and 0.1% ≤ a ≤ 1.8%.
[0054] In nickel-cobalt ternary materials, a larger x (i.e., an increase in nickel content) leads to a decrease in the phase transition temperature, making it easier for the layered phase in the nickel-cobalt ternary material to transform into the rock salt phase, resulting in an increase in the impedance of the nickel-cobalt ternary material. Therefore, this application appropriately reduces the value of a to decrease the thickness ratio between the rock salt phase and the layered phase, which can reduce the impedance of the nickel-cobalt ternary material and improve the fast charging performance of the secondary battery.
[0055] In some embodiments, M is at least one of Al, Mg and Ti, and the mass content of M in the cathode material layer is 300ppm to 30000ppm.
[0056] For example, the mass content of M in the positive electrode material layer can be 300ppm, 500ppm, 1000ppm, 5000ppm, 10000ppm, 15000ppm, 20000ppm, 25000ppm, 30000ppm or any two of these values.
[0057] The secondary battery was discharged to 2.5V at 0.33C. The battery was then disassembled to obtain the positive electrode. The positive electrode was immersed in DMC (dimethyl carbonate) at room temperature for 60 minutes, then removed and air-dried at room temperature with humidity ≤15%. The powder on the dried electrode surface was scraped off with a scraper, preliminarily crushed in a mortar and pestle, and then passed through a 200-mesh sieve to obtain a fine powder sample. A certain amount of powder was accurately weighed and dispersed in 20ml of water, then 10ml of nitric acid was added. After mixing thoroughly, the mixture was heated until the powder dissolved. The solution was then diluted to 100mL with water to obtain the test solution. An ICP test was performed on the test solution. Before testing, a standard solution must be prepared. The linear correlation coefficient of the standard concentration must be above 0.999 to be used as a normal standard. The 0 mg / L standard solution was diluted with deionized water to different concentrations (generally 0, 1 mg / 100 mL, 2 mg / 100 mL, 3 mg / 100 mL), and the element detection wavelength was selected. The experimental conditions were set as follows: Based on the characteristics of the sample and the element to be detected, appropriate ICP instrument operating conditions were set: gas flow rate 0.5 L / min, power 1150 W, and the element detection wavelength was selected, depending on the element being tested (Mg wavelength 285.2 nm, Cr wavelength 267.72 nm, Al wavelength 308.21 nm, Mn wavelength 257.61 nm, Zr wavelength 336.12 nm, Nb wavelength 309.4 nm, Co wavelength 240.7 nm, Ni wavelength 232 nm, Ti wavelength 337.28 nm, V wavelength 292.4 nm). The content of the corresponding dopant element in the sample can be read by the self-analysis function of the ICP testing software.
[0058] In some embodiments, the cathode material layer further includes lithium iron phosphate, wherein the mass percentage of lithium iron phosphate in the cathode material layer is 10-30%.
[0059] For example, the mass percentage of lithium iron phosphate in the cathode material layer can be 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, 20%, 21%, 22%, 23%, 24%, 25%, 26%, 27%, 28%, 29%, 30%, or any two of these values.
[0060] Introducing lithium iron phosphate into the cathode material layer can reduce overall side reactions on the cathode side and improve the cycle performance of the secondary battery.
[0061] In some embodiments, the positive electrode material layer further includes a positive electrode conductive agent and a positive electrode binder.
[0062] Specifically, in the positive electrode material layer, the mass percentage of the positive electrode material is 97.8% to 98.1%, the mass percentage of the positive electrode conductive agent is 0.5% to 1.2%, and the mass percentage of the positive electrode binder is 0.9% to 1.4%.
[0063] The positive electrode conductive agent may include conductive agents conventionally used in the art. For example, the positive electrode conductive agent includes at least one of multi-walled carbon nanotubes, single-walled carbon nanotubes, conductive carbon black, acetylene black, Ketjen black, conductive graphite, graphene, and conductive carbon fiber.
[0064] The positive electrode binder may include positive electrode binders conventionally used in the art. For example, the positive electrode binder includes at least one selected from polytetrafluoroethylene, polyvinylidene fluoride, polyethylene oxide, styrene-butadiene rubber, carboxymethyl cellulose, sodium carboxymethyl cellulose, polyacrylonitrile, polyacrylic acid, sodium polyacrylate, potassium polyacrylate, lithium polyacrylate, polyvinyl alcohol, polyimide, and polyamide-imide.
[0065] The positive current collector may include positive current collectors conventionally used in the art. For example, the positive current collector includes at least one of aluminum foil and composite foil. The composite foil includes a middle high-density layer and metal layers disposed on both sides of the polymer layer. The polymer layer includes polymer materials, including at least one of polyamide (PA), polyterephthalate, polyimide (PI), polyethylene (PE), polypropylene (PP), polystyrene (PPE), polyvinyl chloride (PVC), aramid, acrylonitrile-butadiene-styrene copolymer (ABS), polybutylene terephthalate (PET), poly(p-phenylene terephthalamide) (PPTA), polypropylene (PPE), polyoxymethylene (POM), epoxy resin, phenolic resin, polytetrafluoroethylene (PTEE), polyvinylidene fluoride (PVDF), silicone rubber, polycarbonate (PC), polyvinyl alcohol (PVA), polyethylene glycol (PEG), cellulose, starch, protein, their derivatives, their crosslinks, and their copolymers. The metal layers may include at least one of aluminum, copper, copper alloys, nickel, nickel alloys, titanium, titanium alloys, silver, and silver alloys.
[0066] The positive electrode sheet can be prepared according to conventional methods in the art. For example, the preparation method of the positive electrode sheet includes the following steps: mixing the components of the positive electrode material layer with a solvent to obtain a positive electrode slurry; coating the positive electrode slurry onto two opposing surfaces of a positive electrode current collector aluminum foil; freeze-drying the electrode blank coated with the slurry; and rolling, drying, and cutting the dried electrode blank to obtain the positive electrode sheet.
[0067] In some embodiments, the thickness of the negative electrode material layer is 30 μm to 200 μm.
[0068] For example, the thickness of the negative electrode material layer can be 30μm, 40μm, 50μm, 60μm, 70μm, 80μm, 90μm, 100μm, 110μm, 120μm, 130μm, 140μm, 150μm, 160μm, 170μm, 180μm, 190μm, 200μm or any two sets of values therein.
[0069] In some embodiments, the particle size Dv50 of the negative electrode material is 3μm to 20μm.
[0070] For example, the particle size Dv50 of the negative electrode material can be 3μm, 4μm, 5μm, 6μm, 7μm, 8μm, 9μm, 10μm, 11μm, 12μm, 13μm, 14μm, 15μm, 16μm, 17μm, 18μm, 19μm, 20μm or any two sets of values therein.
[0071] In some embodiments, the particle size Dv99 of the negative electrode material is 18μm~25μm.
[0072] For example, the particle size Dv99 of the negative electrode material can be 18μm, 19μm, 20μm, 21μm, 22μm, 23μm, 24μm, 25μm or any two sets of values therein.
[0073] Through research, the inventors discovered that by adjusting the thickness of the negative electrode material layer and the particle size Dv50 of the negative electrode material to a suitable range, the number of negative electrode material particles per unit thickness of the negative electrode material layer can be moderate. This can reduce the impedance between negative electrode material particles while ensuring a moderate contact area between the negative electrode material particles and the electrolyte, avoiding an excessively large contact area that would cause a sudden increase in side reactions between the negative electrode material particles and the electrolyte. This improves both the fast-charging performance and the cycle performance of the secondary battery.
[0074] In this application, the particle size Dv50 and particle size Dv99 of the negative electrode material can be determined by the following method: The secondary battery was discharged to the lower limit voltage of 2.5V, the secondary battery was disassembled, the negative electrode sheet was removed, and dried at 60℃ for 8 hours. The dried negative electrode sheet was then measured under a scanning electron microscope to obtain the thickness h of the negative electrode material layer on one side, in μm. Discharge the secondary battery to the lower limit voltage of 2.5V, disassemble the secondary battery, remove the negative electrode, dry it at 60℃ for 24 hours, scrape off the powder, take 1g of powder and use a laser particle size distribution measuring instrument (Mastersizer 3000) to measure the particle size distribution according to the particle size distribution laser diffraction method (specific steps refer to GB / T19077-2016). The particle size corresponding to the cumulative particle size distribution percentage of 50% is Dv50, and the particle size corresponding to the cumulative particle size distribution percentage of 99% is Dv99. In some embodiments, the areal density of the negative electrode is 110 g / mm². 2 ~260g / mm 2 .
[0075] For example, the areal density of the negative electrode sheet can be 110 g / mm². 2 120g / mm 2 130g / mm 2 140g / mm 2 150g / mm 2 160g / mm 2 170g / mm 2 180g / mm 2 190g / mm 2200g / mm 2 210g / mm 2 220g / mm 2 230g / mm 2 240g / mm 2 250g / mm 2 260g / mm 2 Or a range consisting of any two sets of values.
[0076] Through research, the inventors discovered that by adjusting the areal density of the negative electrode sheet to a suitable range, this application can ensure the wetting effect of the electrolyte on the negative electrode material layer, reduce the impedance of the negative electrode material layer, and at the same time avoid excessive contact area between the electrolyte and the negative electrode material particles, which would lead to a sudden increase in side reactions, thereby balancing the fast charging performance and cycle performance of the secondary battery.
[0077] The method for testing the areal density of the negative electrode includes, but is not limited to, the following steps: Discharge the secondary battery at 0.33C to the lower limit voltage of 2.5V, disassemble the secondary battery, remove the negative electrode, soak the negative electrode in dimethyl carbonate (DMC) solution for 4 hours, and then air dry. The pretreated negative electrode sheet is punched into circular pieces of a fixed area using a punching machine. The area is recorded as S0. Three circular pieces are taken as parallel samples. The mass of the three circular pieces after soaking for 4 hours is weighed using an electronic balance. The average value is recorded as M1. The thickness of the negative electrode material layer in the three circular pieces (i.e., the total thickness excluding the current collector) is measured using a micrometer. The average value is recorded as H. Finally, an appropriate amount of deionized water is added to each of the three circular pieces. The coating on the circular pieces is gently wiped off with lint-free paper to expose the copper foil. The pieces are left to stand at room temperature (or dried) for 10 minutes. After the copper foil is dry, the mass of the three copper foil pieces is weighed. The average value is recorded as M0. The areal density P of the negative electrode sheet is calculated according to the following formula: P = (M1 - M0) / S0.
[0078] In some embodiments, the specific surface area of the negative electrode material is 0.5 m². 2 / g~3m 2 / g.
[0079] For example, the specific surface area of the negative electrode material can be 0.5 m². 2 / g, 0.6m 2 / g, 0.8m 2 / g、1m 2 / g, 1.2m 2 / g, 1.5m 2 / g, 1.8m 2 / g、2m 2 / g, 2.2m 2 / g, 2.5m 2 / g, 2.8m 2 / g、3m 2 / g or a range consisting of any two sets of values.
[0080] In some embodiments, the negative electrode material includes at least one of graphite, silicon-based materials, and lithium titanate, wherein the graphite includes at least one of natural graphite and artificial graphite, and the silicon-based material includes at least one of elemental silicon, silicon-carbon composite materials, and silicon-oxygen composite materials.
[0081] In some embodiments, the negative electrode material comprises graphite with a particle size Dv50 of 10 μm to 20 μm, and the areal density of the negative electrode sheet is 150 g / mm². 2 ~260g / mm 2 The graphite has a particle size Dv99 of 20μm~25μm.
[0082] In some embodiments, the negative electrode material comprises a silicon-based material with a particle size Dv50 of 3 μm to 15 μm and the areal density of the negative electrode sheet is 110 g / mm². 2 ~200g / mm 2 The particle size Dv99 of the silicon-based material is 18μm~23μm.
[0083] In some embodiments, the negative electrode material layer further includes a negative electrode conductive agent, a negative electrode binder, and a negative electrode dispersant.
[0084] Based on the total mass of the negative electrode material layer, the mass percentage of the negative electrode material is 96%~96.8%, the mass percentage of the negative electrode conductive agent is 1.2%~2.8%, the mass percentage of the negative electrode binder is 1%~2%, and the mass percentage of the negative electrode dispersant is 0.2%~1.5%.
[0085] The negative electrode conductive agent may include conductive agents conventionally used in the art. For example, the negative electrode conductive agent includes at least one of multi-walled carbon nanotubes, single-walled carbon nanotubes, conductive carbon black, acetylene black, Ketjen black, conductive graphite, graphene, and conductive carbon fiber.
[0086] The negative electrode binder may include binders conventionally used in the art. For example, the negative electrode binder includes at least one of polytetrafluoroethylene, polyvinylidene fluoride, polyethylene oxide, styrene-butadiene rubber, carboxymethyl cellulose, sodium carboxymethyl cellulose, polyacrylonitrile, polyacrylic acid, sodium polyacrylate, potassium polyacrylate, lithium polyacrylate, polyvinyl alcohol, polyimide, and polyamide-imide.
[0087] The negative electrode dispersant includes at least one of the following: hydroxymethyl cellulose, acrylic acid, acrylate, polyether ester, phosphate ester, small molecule alkanolamine, polyurethane, modified styrene / maleic anhydride, nitrile rubber (HNBR), and polyvinylpyrrolidone (PVP).
[0088] In some embodiments, the negative electrode sheet includes a negative electrode current collector, and at least one side surface of the negative electrode current collector is provided with the negative electrode material layer.
[0089] The negative electrode current collector may include negative electrode current collectors conventionally used in the art. For example, the negative electrode current collector includes at least one of copper foil, chromium foil, nickel foil, and titanium foil.
[0090] The negative electrode sheet can be prepared according to conventional methods in the art. For example, the preparation method of the negative electrode sheet includes the following steps: mixing negative electrode material, negative electrode conductive agent, negative electrode binder and solvent to obtain negative electrode slurry; coating the negative electrode slurry on at least one side surface of the negative electrode current collector, drying and then rolling and cutting to obtain the negative electrode sheet.
[0091] In some embodiments, the electrolyte contains 0.001% to 3% by mass of cyclic sulfate compounds.
[0092] For example, the mass percentage of cyclic sulfate compounds in the electrolyte can be 0.001%, 0.005%, 0.01%, 0.05%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2%, 2.1%, 2.2%, 2.3%, 2.4%, 2.5%, 2.6%, 2.7%, 2.8%, 2.9%, 3%, or a range of any two sets of values.
[0093] In some embodiments, the electrolyte further includes a solvent and a lithium salt, wherein the concentration of the lithium salt in the electrolyte is 0.5~2 mol / L, and the solvent includes at least one of carbonate solvents, carboxylic acid ester solvents, phosphate ester solvents, ether solvents, nitrile solvents, and sulfone solvents.
[0094] Specifically, the lithium salt includes at least one of lithium hexafluorophosphate, lithium hexafluoroarsenate, lithium tetrafluoroborate, lithium perchlorate, lithium dioxarate borate, lithium difluorooxarate borate, lithium trifluoromethanesulfonate, lithium difluorodioxarate phosphate, lithium tetrafluorooxarate phosphate, lithium difluoromethanesulfonylimide, and lithium ditrifluoromethanesulfonylimide.
[0095] The solvent in the electrolyte includes at least one of carboxylic acid ester solvents, phosphate ester solvents, and fluorinated solvents. The carbonates may include at least one of dimethyl carbonate, diethyl carbonate, methyl ethyl carbonate, ethylene carbonate, and propylene carbonate; the carboxylic acid esters may include at least one of ethyl acetate, methyl formate, methyl propionate, ethyl propionate, propyl propionate, methyl acetate, and 1,4-butyrolactone; and the fluorinated solvents may include at least one of ethyl trifluoroacetate and ethyl difluoroacetate.
[0096] In some embodiments, the electrolyte further includes additives, the additives comprising at least one of methylene disulfonate, vinylene carbonate, 1,3-propanesulfonate lactone, fluoroethylene carbonate, vinyl sulfate, propylene sulfonate lactone, tris(trimethylsilane) phosphate, tris(trimethylsilane) borate, and hexamethylene diisocyanate (HDI), wherein the mass percentage of the additives in the electrolyte is 0.05% to 10%.
[0097] For example, the mass percentage of the additive in the electrolyte can be 0.05%, 0.1%, 0.5%, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, or any two of these values.
[0098] In some embodiments, the battery cell further includes a separator located between the positive electrode and the negative electrode. The separator may include a substrate layer comprising at least one of polyethylene, polypropylene, polyamide, and aramid.
[0099] Optionally, the diaphragm may further include an adhesive layer and / or a ceramic layer. The adhesive layer may be made of at least one of polyvinylidene fluoride, polymethyl methacrylate, aramid, polyethylene oxide, polyvinylidene fluoride-hexafluoropropylene copolymer, or polyaniline; the ceramic layer may be made of at least one of boehmite, alumina, titanium dioxide, silicon dioxide, zirconium dioxide, tin dioxide, magnesium oxide, zinc oxide, barium sulfate, boron nitride, aluminum nitride, and magnesium nitride.
[0100] In some embodiments, the secondary battery further includes tabs, the width of which is 0.1 to 1 compared to the length of the cell, which can improve the fast-charging performance of the secondary battery.
[0101] For example, the ratio between the width of the tab and the length of the cell can be 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1, or any two sets of values therein.
[0102] In some of these embodiments, when the tab is located at one end of the cell along its length, the ratio between the width of the tab and the length of the cell is preferably 0.2 to 1. When the tab is located at one end of the cell height direction, the ratio between the width of the tab and the length of the cell is preferably 0.1 to 0.4.
[0103] In this application, the cell height direction, cell length direction, and cell thickness direction of the secondary battery are perpendicular to each other.
[0104] In some embodiments, the thickness of the tab is 4 μm to 18 μm.
[0105] For example, the thickness of the electrode tab can be 4μm, 5μm, 6μm, 7μm, 8μm, 9μm, 10μm, 11μm, 12μm, 13μm, 14μm, 15μm, 16μm, 17μm, 18μm or any two sets of values therein.
[0106] In some embodiments, the secondary battery includes a casing, and the wall thickness of the casing is 0.2 mm to 1 mm in the thickness direction of the battery cell.
[0107] It is understandable that the thickness direction of the battery cell is the stacking direction of the positive electrode, separator, and negative electrode in the battery cell. When the battery cell is a wound battery cell, the wound battery cell includes a straight section and a bent section, and the thickness direction of the battery cell is the stacking direction of the positive electrode, separator, and negative electrode in the straight section of the battery cell.
[0108] For example, the wall thickness of the shell can be 0.2mm, 0.3mm, 0.4mm, 0.5mm, 0.6mm, 0.7mm, 0.8mm, 0.9mm, 1mm or any two sets of values therein.
[0109] This application, by adjusting the wall thickness of the casing, can ensure that the casing has greater strength and better resistance to deformation, so that the casing does not deform or deforms only slightly when the pressure increases due to gas production from side reactions inside the secondary battery.
[0110] In some embodiments, the housing is used to encapsulate components such as electrode assemblies and electrolytes. The housing can be made of steel, aluminum, plastic (such as polypropylene), composite metal (such as copper-aluminum composite), or aluminum-plastic film, etc.
[0111] In a second aspect, this application provides an electrical device including the aforementioned secondary battery.
[0112] To enable those skilled in the art to better understand the present application, the technical solutions in the embodiments of the present application will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present application, and not all embodiments.
[0113] In the following examples and comparative examples, the structural formula of compound 1 is as follows: The structural formula of compound 2 is The structural formula of compound 3 is The structural formula of compound 4 is The structural formula of compound 5 is The structural formula of compound 6 is .
[0114] Unless otherwise specified, all components and raw materials used in the embodiments and comparative examples of this application are commercially available, and the same type of components and raw materials are used in each parallel experiment.
[0115] Example 1 The embodiment of the lithium-ion secondary battery described in this application includes a method for preparing the lithium-ion secondary battery comprising the following steps: S1, Preparation of nickel-cobalt ternary materials: According to the molar ratios in the chemical formulas of the nickel-cobalt ternary materials in Table 1, the sulfates of each metal element were dissolved in deionized water and mixed evenly to prepare a metal salt solution with a concentration of 2 mol / L for all metal elements. The metal salt solution was then mixed with 2 mol / L of precipitant (NaOH) and 2 mol / L of complexing agent (NH3·H2O). The pH of the reaction system was adjusted to 11, and the co-precipitation reaction was carried out at 120℃ for 24 h. After drying, the precursor was obtained. Lithium hydroxide was mixed with the obtained precursor. The amount of lithium in the lithium hydroxide was MLi, and the total amount of metal in the metal salt solution was Me. Based on the molar ratio, MLi:Me = 1.05:1. The mixed material was sintered in an oxygen atmosphere. The sintering temperature and sintering time are shown in Table 1. After cooling to room temperature, the material was crushed and sieved to obtain the nickel-cobalt ternary material with the chemical formula shown in Table 1.
[0116] S2, Preparation of the positive electrode: Nickel-cobalt ternary material, conductive carbon black SP, binder polyvinylidene fluoride (PVDF), and polyvinylpyrrolidone (PVP) were mixed in a mass ratio of nickel-cobalt ternary material: conductive carbon black SP: PVDF: PVP = 96:1:2:1. N-methylpyrrolidone (NMP) was added, and the mixture was stirred under vacuum until the system was homogeneous, resulting in a positive electrode slurry with a solid content of 70%. The positive electrode slurry was coated onto two opposite surfaces of a positive electrode current collector aluminum foil, and after drying, rolling, and cutting, a positive electrode sheet with an areal density of 220 g / m³ was obtained. 2 .
[0117] S3. Preparation of the negative electrode: The selection of negative electrode materials is shown in Table 2. The negative electrode materials were milled. The negative electrode materials, conductive carbon black (SP), carboxymethyl cellulose (CMC), and styrene-butadiene rubber (SBR) were mixed in a mass ratio of negative electrode material:SP:SBR:CMC = 96.4:1.2:1.4:1. Deionized water was added, and the mixture was stirred under vacuum until homogeneous, yielding a negative electrode slurry with a solid content of 70%. This negative electrode slurry was coated onto two opposing surfaces of a copper foil along its thickness direction. After drying, cold pressing, and cutting, a negative electrode sheet was obtained with an areal density of 140 g / m³. 2 .
[0118] S4. Preparation of electrolyte: Ethylene carbonate (EC) and ethyl methyl carbonate (EMC) were mixed at a volume ratio of 7:3 to obtain an organic solvent. Then, the cyclic sulfate compounds shown in Table 1 were dissolved in the mixed organic solvent. Next, fully dried lithium salt LiPF6 was added to prepare an electrolyte. The concentration of lithium salt LiPF6 in the electrolyte was 1.1 mol / L, and the mass percentage of the cyclic sulfate compounds was shown in Table 2.
[0119] S5. Preparation of the diaphragm: Commercially available PE membrane was chosen as the separator, with a thickness of 9μm.
[0120] S6. Stack the obtained positive electrode sheet, separator, and negative electrode sheet in sequence, so that the separator is between the positive electrode sheet and the negative electrode sheet to play a role in isolation, and then wind them to obtain a bare cell; put the bare cell into an aluminum shell, dry it, inject electrolyte, and then go through vacuum sealing, standing, formation, shaping and other processes to obtain a lithium-ion secondary battery.
[0121] Examples 2-30 and Comparative Examples 1-6 The differences between Examples 2-30 and Comparative Examples 1-6 and Example 1 are as follows: The chemical formula of the nickel-cobalt ternary material in step S1 of Example 11 is shown in Table 1; the chemical formula of the nickel-cobalt ternary material in step S1 of Examples 23-24 is shown in Table 1; the sintering temperature and sintering time in step S1 of Examples 2-30 and Comparative Examples 1-6 are shown in Table 1. In step S2 of Example 29, nickel-cobalt ternary material, lithium iron phosphate, conductive carbon black SP, binder polyvinylidene fluoride (PVDF) and polyvinylpyrrolidone (PVP) are mixed in a mass ratio of nickel-cobalt ternary material: lithium iron phosphate: conductive carbon black SP: PVDF: PVP = 85.7: 10.3: 1: 2: 1 (i.e., the mass percentage of lithium iron phosphate in the cathode material layer is 10.3%). In step S2 of Example 30, nickel-cobalt ternary material, lithium iron phosphate, conductive carbon black SP, binder polyvinylidene fluoride (PVDF) and polyvinylpyrrolidone (PVP) are mixed in a mass ratio of nickel-cobalt ternary material: lithium iron phosphate: conductive carbon black SP: PVDF: PVP = 67.4: 28.6: 1: 2: 1 (i.e., the mass percentage of lithium iron phosphate in the cathode material layer is 28.6%). Examples 2-30 and Comparative Examples 1-6 changed the thickness of the negative electrode material layer by adjusting the coating amount of the negative electrode slurry and the cold pressing pressure in step S3, as detailed in Table 2; Examples 25-26 and Comparative Example 6 changed the type of negative electrode material, as detailed in Table 2; Examples 2-30 and Comparative Examples 1-6 changed the particle size Dv50 of the negative electrode material by adjusting the milling time, as detailed in Table 2. Examples 2-30 and Comparative Examples 1-6 adjusted the types and amounts of cyclic sulfate compounds in step S4 to achieve the mass percentage content of cyclic sulfate compounds and the mass percentage content of sulfate groups in the electrolyte, as shown in Table 2.
[0122] In Examples 1-30 and Comparative Examples 1-6 above, at least one of the following—the content of nickel and the content of doping elements (i.e., the molar ratio of each metal element in the chemical formula of the nickel-cobalt ternary material), sintering temperature, and sintering time—is adjusted in step S1 to change the primary particle diameter d and the thickness e of the surface rock salt phase of the primary particles, thereby changing a. In step S3, the grinding time is adjusted to change the particle size Dv50 of the negative electrode material. In step S3, the coating amount of the negative electrode slurry and the cold pressing pressure are adjusted to change the thickness of the negative electrode material layer. The changes in the particle size Dv50 and / or the thickness of the negative electrode material layer change b. In step S4, the type and amount of cyclic sulfate compounds are adjusted to change the mass percentage of cyclic sulfate compounds and the mass percentage of sulfate groups c in the electrolyte.
[0123] This application uses the secondary batteries obtained in various embodiments and comparative examples as test objects, and conducts relevant performance tests. The test results are shown in Tables 1-3, and the test methods are as follows: 1. Discharge the secondary battery to the lower limit voltage of 2.5V, disassemble the secondary battery, and remove the positive electrode plate; The cathode sheet was subjected to TEM scanning. Random blind scanning high-magnification (100Kx~200Kx, i.e., 100,000 to 200,000 times) transmission electron microscopy was performed on the edges of the nickel-cobalt ternary material particles to obtain lattice fringe images at the particle edges. The lattice fringe spacing at the edges was measured using MEARSURE NANO software. The distribution area with a lattice fringe spacing of 0.207±0.01nm (the lattice spacing of Fd3m in Ni-O) can be identified as Ni-O in the Fd3m (rock salt phase) space group. In addition, the inner side of the Fd3m phase refers to the layered phase (Fr3m), and the lattice fringe spacing of the layered phase is selected as 0.473 ± 0.01nm. Five particles were taken, and the thickness of Fd3m (rock salt phase) at 10 locations on the same particle was measured. The average value was then taken to obtain the average thickness of Fd3m (rock salt phase) (denoted as e). Then the magnification of the transmission electron microscope was adjusted to 2kx (i.e., 2000 times), and MEARSURE was used to measure the thickness of the Fd3m (rock salt phase) at the same location. The NANO software uses the cross-hatching method to collect the particle diameter (denoted as d) of the nickel-cobalt ternary material. The a1% of the particle is calculated according to the formula (1); a1%=(e / d)×100% (1). The a1% of 5 particles is measured and the average value is taken as a.
[0124] 2. Discharge the secondary battery to the lower limit voltage of 2.5V, disassemble the secondary battery, remove the negative electrode sheet, dry it at 60℃ for 8 hours, and then measure the thickness h (in μm) of the negative electrode material layer on one side using a scanning electron microscope. Discharge the secondary battery to the lower limit voltage of 2.5V, disassemble the secondary battery, remove the negative electrode, dry it at 60℃ for 24 hours, scrape off the powder, take 1g of powder and use a laser particle size distribution measuring instrument (Mastersizer 3000) to measure the particle size distribution according to the particle size distribution laser diffraction method (specific steps refer to GB / T19077-2016). The particle size corresponding to the cumulative particle size distribution percentage reaching 50% is Dv50 (unit is μm). The value of b can be calculated using the formula b=h / Dv50.
[0125] 3. Use a battery charging and discharging device to discharge the secondary battery under test. Discharge conditions: current 0.33C, cutoff voltage 2.5V. After recording the battery number / barcode, disassemble the battery in a glove box (where the molar content of H2O ≤ 0.1ppm and the molar content of O2 ≤ 0.1ppm) to collect the electrolyte. There are three methods for collecting the electrolyte: After removing the battery cover, ① if there is free electrolyte, collect the electrolyte into a 5mL sample tube with a pipette and seal it with sealing tape to prevent electrolyte leakage. ② if there is no free electrolyte, use a hydraulic press (Beijing Heng'ao Technology Co., Ltd.'s FY-30 hydraulic press) to continuously pressurize until free electrolyte appears, collect the electrolyte into a sample tube and seal it. ③ Add an appropriate amount of dichloromethane extractant to the battery and record the dichloromethane content. After adding dichloromethane, put the battery into an aluminum-plastic bag and seal it with a heat sealer. Transfer it to an ultrasonic oscillator and oscillate for 12 hours to allow the electrolyte in the electrode to mix thoroughly with the dichloromethane. Then, use a pipette to draw the mixture of dichloromethane and electrolyte into a 5mL sample tube and seal the sample tube with sealing glue. The collected electrolyte samples were injected into an Agilent Intuvo 9000 gas chromatograph-mass spectrometer using a microsyringe for testing, and GC-MS spectra were obtained. Cyclic sulfate ester compound standards were dissolved in EMC solvent to prepare solutions of different concentrations, and these solutions were injected into the Agilent Intuvo 9000 gas chromatograph-mass spectrometer to obtain standard GC-MS spectra. The GC-MS spectra of the electrolyte samples were compared with the standard GC-MS spectra to confirm whether the electrolyte samples contained the corresponding cyclic sulfate ester compounds, and their relative molar mass M1 was obtained. Based on the determined structural formula of the cyclic sulfate ester compound, determine the number of sulfate ester groups and the relative molar mass M2 of the sulfate ester groups in the structural formula; The mass percentage (denoted as C) of cyclic sulfate ester compounds in the electrolyte was obtained by using GC gas chromatography based on the measured components. The mass percentage c of sulfate groups in the electrolyte is calculated using the following formula: c = (M2 / M 1) ×n×C.
[0126] IV. Cycle performance of secondary batteries: In a 25°C environment, the secondary battery is charged at a constant current of 1C to the upper limit voltage of 4.25V, and then charged at a constant voltage of 4.25V until the current is ≤0.05mA. After resting for 5 minutes, the secondary battery is discharged at a constant current of 1C to the lower limit voltage of 2.5V. This is the first charge-discharge cycle of the secondary battery, and the discharge capacity of this cycle is recorded as the discharge capacity of the secondary battery in the first cycle (C0). After resting for 20 minutes, the above steps are repeated for the secondary battery, and the discharge capacity of the secondary battery after the 500th cycle (C1) is recorded. The discharge capacity retention rate of the secondary battery after 500 cycles is C1 / C0×100%.
[0127] V. Fast charging performance of secondary batteries: The battery charging and discharging equipment performs a discharge process on the secondary battery. The discharge conditions are: discharge at a current of 0.33C to the lower limit voltage of 2.5V, and then charge and discharge at 0.33C for 3 cycles to determine the capacity. The voltage range is 2.5V~4.25V. The discharge capacity of the third cycle is taken as the battery capacity. Then, after charging to 5% SOC at 0.33C, a fast charging test was conducted, specifically as follows: charging at 3C to 10% SOC, recording the charging time for this stage as t1; charging at 5C to 15% SOC, recording the charging time for this stage as t2; charging at 4.5C to 20% SOC, recording the charging time for this stage as t3; charging at 4C to 40% SOC, recording the charging time for this stage as t4; charging at 4C to 50% SOC, recording the charging time for this stage as t5; then charging at 3.5C to 60% SOC, recording the charging time for this stage as t6; charging at 3C to 70% SOC, recording the charging time for this stage as t7; charging at 2C to 80% SOC, recording the charging time for this stage as t8; then charging at 1.5C to 85% SOC; then charging at 1C to 90% SOC; then charging at 0.5C to 95% SOC; and finally charging at 0.33C to 100% SOC. Fast charging time t = t1 + t2 + t3 + t4 + t5 + t6 + t7 + t8.
[0128] Table 1 Table 2 Table 3 As can be seen from Tables 1-3, the embodiments of this application, by introducing cyclic sulfate compounds into the electrolyte and comprehensively controlling the ratio a of the nickel-cobalt ternary material, the ratio b between the thickness of the negative electrode material layer and the particle size Dv50 of the negative electrode material, and the mass percentage content c of sulfate functional groups in the electrolyte, ensure that a / (b×c) is within a suitable range. This effectively improves the fast-charging performance and cycle performance of the secondary battery. The charging time required for the secondary battery to go from 10% to 80% SOC is ≤24.9 min, and the discharge capacity retention rate after 500 cycles is ≥75.1%. When 0.0016≤a / (b×c)≤73.2353, 0.12%≤a≤1.5%, 2≤b≤35, and 0.01%≤c≤2.5%, the fast-charging performance and cycle performance of the secondary battery can be better balanced.
[0129] Compared with the embodiments, in Comparative Example 1, a / (b×c) is too small, and a is too small while c is too large, which leads to a significant decrease in the cycle performance of the secondary battery.
[0130] Compared with the embodiments, in Comparative Example 2, a / (b×c) is too large and b is too small, which leads to a decrease in the fast charging performance of the secondary battery.
[0131] Compared with the embodiments, in Comparative Example 3, a / (b×c) is too small, and a is too small while b and c are too large, which leads to a decrease in the cycle performance of the secondary battery, even worse than the cycle performance of Comparative Example 1.
[0132] Compared with the embodiments, in Comparative Example 4, a / (b×c) is too large, and a is too large while b is too small, which leads to a decrease in the fast charging performance of the secondary battery, and even worse than the fast charging performance of Comparative Example 2.
[0133] Compared with the embodiments, Comparative Example 5 did not introduce cyclic sulfate compounds into the electrolyte, resulting in a significant decrease in both the fast charging performance and cycle performance of the secondary battery.
[0134] Compared with the embodiments, in Comparative Example 6, a / (b×c) is too large and b is too small, which leads to a decrease in the fast charging performance of the secondary battery.
[0135] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of this application and are not intended to limit the scope of protection of this application. Although this application has been described in detail with reference to preferred embodiments, those skilled in the art should understand that modifications or equivalent substitutions can be made to the technical solutions of this application without departing from the substance and scope of the technical solutions of this application.
Claims
1. A secondary battery, characterized in that, The battery includes a battery cell and an electrolyte. The battery cell includes a positive electrode and a negative electrode. The positive electrode includes a positive electrode material layer, which is a nickel-cobalt ternary material with a specific gravity of 'a'. The nickel-cobalt ternary material comprises primary particles, each primary particle including a core and a surface layer disposed on the outer surface of the core. The diameter of the primary particles is 'd' (in nm). The surface layer of the primary particles is a rock salt phase with a thickness of 'e' (in nm). 'a' is 'e / d' × 100%. The negative electrode sheet includes a negative electrode material layer, the negative electrode material layer includes a negative electrode material, the ratio between the thickness of the negative electrode material layer and the particle size Dv50 of the negative electrode material is b, and the units of the thickness of the negative electrode material layer and the particle size Dv50 of the negative electrode material are both μm; The electrolyte includes cyclic sulfate ester compounds. The mass percentage of sulfate ester functional groups in the electrolyte is c. The method for testing c is as follows: the electrolyte sample is tested by gas chromatography-mass spectrometry to determine the structural formula and mass percentage of the cyclic sulfate ester compounds in the electrolyte. The mass percentage of sulfate ester groups in the electrolyte is calculated according to the following formula: c = (M2 / M1) × n × C, where C is the mass percentage of the cyclic sulfate ester compounds in the electrolyte, M1 is the relative molar mass of the cyclic sulfate ester compounds, n is the number of sulfate ester groups in the structural formula of the cyclic sulfate ester compounds, and M2 is the relative molar mass of the sulfate ester groups. The secondary battery satisfies the following conditions: 0.0016≤a / (b×c)≤73.2353, 0.12%≤a≤1.5%, 2≤b≤35, 0.01%≤c≤2.5%; The cyclic sulfate compounds include compounds represented by Formula I; in Formula I, R1, R2, R3 and R4 each independently include at least one of the following groups represented by Formula II, hydrogen atoms, alkyl groups of 1 to 6 carbon atoms, halogen atoms, haloalkyl groups of 1 to 3 carbon atoms, alkoxy groups of 1 to 3 carbon atoms, haloalkoxy groups of 1 to 3 carbon atoms, alkenyl groups, ester groups, cyano groups, and sulfonic acid groups; In Formula II, R5 and R6 each independently include at least one of the following groups as shown in Formula III: a hydrogen atom, an alkyl group of 1 to 6 carbon atoms, a halogen atom, a haloalkyl group of 1 to 3 carbon atoms, an alkoxy group of 1 to 3 carbon atoms, a haloalkoxy group of 1 to 3 carbon atoms, an alkenyl group, an ester group, a cyano group, and a sulfonic acid group. In Formula III, R7 and R8 each independently include at least one of the following: hydrogen atom, alkyl group of 1 to 6 carbon atoms, halogen atom, haloalkyl group of 1 to 3 carbon atoms, alkoxy group of 1 to 3 carbon atoms, haloalkoxy group of 1 to 3 carbon atoms, alkenyl group, ester group, cyano group, and sulfonic acid group. Formula I, Formula II, Formula III.
2. The secondary battery as described in claim 1, characterized in that, In the compound shown in Formula I, the number of sulfate ester groups is n, where n is a positive integer from 2 to 4.
3. The secondary battery as described in claim 1, characterized in that, At least one of R2 and R4 is a hydrogen atom, and R1 and R3 each independently include at least one of the following: a group represented by Formula II, a hydrogen atom, an alkyl group of 1 to 6 carbon atoms, a halogen atom, a haloalkyl group of 1 to 3 carbon atoms, and an alkoxy group of 1 to 3 carbon atoms.
4. The secondary battery as described in claim 3, characterized in that, R1 and R3 are the same substituents, and are selected from any one of the groups shown in Formula II, hydrogen atoms, alkyl groups of 1 to 6 carbon atoms, halogen atoms, haloalkyl groups of 1 to 3 carbon atoms, and alkoxy groups of 1 to 3 carbon atoms.
5. The secondary battery as described in claim 4, characterized in that, R1 and R3 are selected from -CH3, -C2H5, -C3H7, -CH=CH2, -CH2-CH=CH2, -CH=CH-CH3, -O-CH3, -O-C2H5, -O-C3H7, -F, -Cl, -Br, -I, -CF3, -CCl3, -CBr3, -C2F5, -C2Cl5, -C2Br5, -C3F7, -C3Cl7, -C3Br7. Any one of the groups shown.
6. The secondary battery as described in claim 1, characterized in that, The diameter of the primary particle is 2000nm~20000nm, and / or the thickness of the surface layer of the primary particle is 0.8nm~50nm.
7. The secondary battery as described in claim 1, characterized in that, The compacted density of the positive electrode sheet is 3 g / cm 3 4 g / cm 3 .
8. The secondary battery as described in claim 1, characterized in that, The chemical general formula of the nickel-cobalt ternary material is LiNi x Co y Mn z M f O2, wherein 0.1 x+y+z+f=1, M is a doping element, and M includes at least one of Al, Mg, Ti, Zr, B, P, Nb, Ta, W, Zr, and V.
9. The secondary battery as described in claim 8, characterized in that, M is at least one of Al, Mg and Ti, and the mass content of M in the cathode material layer is 300ppm to 30000ppm.
10. The secondary battery as described in claim 1, characterized in that, The cathode material layer also includes lithium iron phosphate, and the mass percentage of lithium iron phosphate in the cathode material layer is 10% to 30%.
11. The secondary battery as described in claim 1, characterized in that, The thickness of the negative electrode material layer is 30μm~200μm; And / or, the particle size Dv50 of the negative electrode material is 3μm~20μm; And / or, the particle size Dv99 of the negative electrode material is 18μm~25μm.
12. The secondary battery as described in claim 1, characterized in that, The areal density of the negative electrode is 110 g / mm². 2 ~260g / mm 2 .
13. The secondary battery as described in claim 1, characterized in that, The specific surface area of the negative electrode material is 0.5 m². 2 / g~3m 2 / g.
14. The secondary battery as described in claim 1, characterized in that, The negative electrode material includes at least one of graphite, silicon-based materials, and lithium titanate. The graphite includes at least one of natural graphite and artificial graphite. The silicon-based material includes at least one of elemental silicon, silicon-carbon composite materials, and silicon-oxygen composite materials.
15. The secondary battery as described in claim 14, characterized in that, The negative electrode material includes graphite with a particle size Dv50 of 10 μm to 20 μm, and the areal density of the negative electrode sheet is 150 g / mm². 2 ~260g / mm 2 The graphite has a particle size Dv99 of 20μm~25μm.
16. The secondary battery as described in claim 14, characterized in that, The negative electrode material includes a silicon-based material with a particle size Dv50 of 3μm to 15μm and an areal density of 110g / mm². 2 ~200g / mm 2 The particle size Dv99 of the silicon-based material is 18μm~23μm.
17. The secondary battery as described in claim 1, characterized in that, The electrolyte contains 0.001% to 3% by mass of cyclic sulfate compounds.
18. The secondary battery as described in claim 1, characterized in that, The electrolyte further includes a solvent and a lithium salt. The concentration of the lithium salt in the electrolyte is 0.5~2 mol / L. The lithium salt includes at least one of lithium hexafluorophosphate, lithium hexafluoroarsenate, lithium tetrafluoroborate, lithium perchlorate, lithium dioxalate borate, lithium difluorooxalate borate, lithium trifluoromethanesulfonate, lithium difluorodioxalate phosphate, lithium tetrafluorooxalate phosphate, lithium difluoromethanesulfonylimide, and lithium ditrifluoromethanesulfonylimide. The solvent includes at least one of carbonate solvents, carboxylic acid ester solvents, and fluorinated solvents.
19. The secondary battery as described in claim 1, characterized in that, The electrolyte further includes additives, which include at least one of the following: methylene disulfonate, vinylene carbonate, 1,3-propanesulfonate lactone, fluoroethylene carbonate, vinyl sulfate, propylene sulfonate lactone, tris(trimethylsilane) phosphate, tris(trimethylsilane) borate, and hexamethylene diisocyanate. The mass percentage of the additives in the electrolyte is 0.05% to 10%.
20. The secondary battery as described in claim 1, characterized in that, The secondary battery also includes tabs, and the ratio between the width of the tabs and the length of the battery cell is 0.1 to 1.
21. The secondary battery as described in claim 20, characterized in that, The thickness of the electrode tab is 4μm~18μm.
22. The secondary battery as described in claim 1, characterized in that, The secondary battery includes a casing, and the wall thickness of the casing is 0.2mm to 1mm in the thickness direction of the battery cell.
23. An electrical appliance, characterized in that, Includes the secondary battery as described in any one of claims 1 to 22.
Citation Information
Patent Citations
Positive electrode material, and electrochemical device and electronic apparatus using same
CN114551857A
Lithium ion battery
CN121484167A